High-capacity and high-rate polycrystalline ternary positive electrode material, preparation method thereof and battery
Through multi-stage sintering and doping coating technology, the structural instability and lithium-nickel mixed discharge problems of lithium-ion battery ternary cathode materials under high nickelization and high voltageization are solved, and the performance improvement of high capacity and high magnification is achieved , reduces production costs.
Patent Information
- Application Number
- CN202411586341.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The ternary cathode materials of existing lithium-ion batteries have problems such as structural instability, increased risk of spontaneous combustion and serious lithium-nickel mixed discharge during the high nickel and high voltage. It is difficult to meet the needs of high capacity and high magnification, and at the same time, the high temperature solidification The phase reaction synthesis method is costly and difficult to produce.
Using the interaction between the multi-stage sintering platform and the doping elements and the coating elements, the lithium-nickel mixing inhibition, crystal structure stability and rate performance can be improved through the combination of dopants A, coating agents B and C, and the high capacity is prepared. High-magnification polycrystalline ternary cathode material.
Effectively suppress lithium-nickel mixed discharge, improve the structural stability and rate performance of the positive electrode material, reduce production costs, and meet the needs of high capacity and high rate.
Smart Images

Figure CN119118223A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a high-capacity and high-rate polycrystalline ternary positive electrode material and a preparation method and a battery thereof. Background Art
[0002] With the emergence and development of new things such as power tools, electric vehicles (EVs) and smart grids, the demand for the development of lithium-ion batteries with high energy density, high power density and long cycle life has become more and more urgent. In order to solve the range anxiety, high nickel content and high voltage are usually used to improve energy density. However, high nickel content often leads to instability in the structure of positive electrode materials, increasing the probability of spontaneous combustion. The increase in nickel content will also be sensitive to moisture, which often requires the production environment to have higher requirements for moisture control.
[0003] At present, the conventional 6-series ternary materials are mainly NCM613 and NCM622. The Ni ratio of the two 6-series ternary materials accounts for 60% of the metal ratio, and the 0.5C specific capacity can reach 170mAh / g, but it is still difficult to meet the current lithium-ion battery capacity requirements. At the same time, due to the reaction characteristics of high-nickel materials, it is often required to use a lower temperature + oxygen atmosphere for high-temperature solid-phase reaction in production, which greatly increases the production cost and difficulty.
[0004] In addition, the conventional high-temperature solid-phase reaction synthesis method of ternary materials is a simple double-platform heating to the final high-temperature reaction temperature, continuous heat preservation for more than ten hours and then cooling to obtain the finished product. The required sintering time is long and the cost is high. The long-term high-temperature reaction also leads to serious lithium-nickel mixing in ternary materials, especially high-nickel materials, which seriously affects the material performance.
[0005] Prior art 1: Chinese patent application 202410098770.8 discloses a ternary positive electrode material and a preparation method thereof, the preparation method comprising the following steps: A nickel-cobalt-manganese ternary precursor and a lithium source are mixed and then subjected to a first sintering treatment to obtain a positive electrode material precursor; The positive electrode material precursor is mixed with urea and then subjected to a second sintering treatment to obtain the ternary positive electrode material.
[0006] This scheme uses an appropriate amount of urea to coat the ternary cathode material precursor and sinter it under an inert gas. Under an inert atmosphere, urea will be carbonized after calcination and form a carbon coating layer on the surface of the cathode material precursor sample; Further observation of the scheme shows that the first sintering process in the scheme includes: The first stage of sintering includes heating to 650-750°C at a heating rate of 1.5-2.5°C / min; The second stage of sintering includes heating to 850-900°C at a heating rate of 0.5-1°C / min and keeping the temperature for 10-14h; The third stage of sintering includes cooling to 650-750°C at a cooling rate of 0.5-1°C / min and then cooling with the furnace; Further observation of the description of staged sintering in paragraph 56 of the specification of this scheme shows that its purpose is: "The lithium mixing method of staged heating can make the lithium source and the nickel-cobalt-manganese ternary precursor mix more evenly, and can also reduce the amount of residual lithium on the surface of the material, thereby improving the electrochemical performance of the battery."
[0007] Prior art 2: Chinese patent application 202410672263.0 discloses a ternary polycrystalline positive electrode material and a preparation method thereof, a lithium-ion battery and an electrical device, comprising a ternary positive electrode material matrix and a composite oxide coating layer coated on the surface of the matrix, wherein the composite oxide coating layer is rich in Co, Nb, and M3 elements, and the M3 element is selected from at least one of Si, W, Sn, La, Zr, Ce, Mg and Al.
[0008] The preparation method comprises: mixing a ternary precursor material, a lithium source and a compound containing an M2 element and sintering the mixture to obtain a sintered material; mixing the sintered material with a cobalt source, a niobium source and a compound containing an M3 element and sintering the mixture to obtain a ternary polycrystalline positive electrode material; The M2 elements include Zr, Sr, W, Al, Ti, Mo, Ce, Ca, Ta and Mg; In this solution, niobium is used as a coating layer rather than as a dopant.
[0009] The problem that this solution needs to solve is: how to provide a method for preparing a polycrystalline ternary positive electrode material with high capacity and high rate. Summary of the invention
[0010] The purpose of this application is to provide a method for preparing a high-capacity and high-rate polycrystalline ternary positive electrode material. This method improves the capacity and rate performance of the polycrystalline ternary positive electrode material from multiple aspects such as crystal structure stability, lithium-nickel mixing degree, lithium dispersion uniformity, and stability of the positive electrode material itself through the interaction between multiple sintering platforms and doping elements, coating elements, and ternary materials.
[0011] Unless otherwise specified in this application: nM represents nanomole / liter, μM represents micromole / liter, mM represents millimole / liter, and M represents mole / liter; To achieve the above objectives, the present application discloses a method for preparing a high-capacity and high-rate polycrystalline ternary cathode material, comprising the following steps: Step 1: Mixing the nickel-cobalt-manganese precursor with the dopant A and the lithium source, and sintering once to obtain a single-fired material; Step 2: crushing the first-fired material, then mixing it with coating agent B and coating agent C, and sintering it twice to obtain a high-capacity and high-rate polycrystalline ternary positive electrode material; The primary sintering process includes a first heat preservation platform, a second heat preservation platform and a third heat preservation platform; The temperature of the first insulation platform is 660-700°C, and the insulation time is 1.5-2.5h; The temperature of the second insulation platform is 850-900°C, and the insulation time is 1.5-2.5h; The temperature of the third insulation platform is 750-790°C, and the insulation time is 4-6h; The dopant A is selected from at least one of compounds containing niobium, zirconium, yttrium and strontium; The coating agent B is selected from at least one of compounds containing boron and cobalt; The coating agent C is selected from at least one of compounds containing silicon and aluminum.
[0012] By adding the dopant A to the material before the primary sintering, the melting point of the lithium source is lowered, the penetration of lithium in the material is improved, and the lithium distribution is made more uniform. At the same time, since the dopant A can enter the crystal lattice of the primary sintered material and play a stabilizing role, it can also effectively inhibit the adverse effects of lithium-nickel mixing on the positive electrode material. At the same time, due to the fluxing effect of dopant A, it is not necessary to maintain high temperature sintering throughout the first sintering process. As the first insulation platform with relatively low temperature, the reactants (Li2O, NCMO) decomposed during the sintering process can undergo a preliminary reaction. The mild reaction at this relatively low reaction temperature can obtain primary grains with uniform size and complete results, which lays a good foundation for the sufficient growth of grains under subsequent high temperature conditions, and finally it is easy to obtain a finished positive electrode material with uniform primary particle size and complete lattice. Further, the second insulation platform with a relatively high temperature makes it easier for the dopant A to enter the lattice of the positive electrode material. At the same time, the second insulation platform with a relatively high temperature can promote the rapid growth of the grains so that the grains grow into primary particles with a volume close to the expected target in a short time; finally, the growth of the grains is further promoted by cooling and sintering. More importantly, the third insulation platform with a relatively long time can inhibit the lithium-nickel mixing phenomenon and repair the internal defects of the primary particles due to its relatively low temperature, thereby improving the structural stability of the primary particles; At the same time, the surface of the fired material is coated. On the one hand, both coating agents can form a fast ion conductor coating layer on the surface of the positive electrode material, which not only improves the protection ability of the positive electrode material, but also can improve the rate performance of the material to a certain extent. In addition, some elements in the coating layer will also partially enter the lattice, further repairing the internal defects of the primary particles; Preferably, the chemical formula of the nickel-cobalt-manganese precursor is Ni X Co Y Mn Z (OH)2, where 0.60≤x≤0.70, 0.10≤y≤0.20, 0.20≤z≤0.30 and x+y+z=1; When the above design is applied to the medium nickel ternary positive electrode material with a nickel content of 0.6-0.7, its ability to inhibit lithium-nickel mixing is more prominent. The reason may be that the lithium-nickel mixing phenomenon increases with the increase of nickel content. The low nickel ternary material has a relatively low nickel content, so the lithium-nickel mixing is relatively not serious. However, high-nickel materials or ultra-high-nickel materials have a higher nickel content, which leads to excessive lithium-nickel mixing. Even if they can inhibit it, the inhibitory effect is not obvious compared with medium-nickel materials. Preferably, the chemical formula of the nickel-cobalt-manganese precursor is Ni X Co Y Mn Z (OH)2, where 0.65≤x<0.70, 0.10<y≤0.15, z=0.20 and x+y+z=1. Further, when the nickel material is a medium nickel ternary material with a partial ratio (the molar ratio of cobalt and manganese is not 1:1), it will have higher capacity performance than the conventional NCM622 material, but it will also face a more serious risk of lithium-nickel mixing, and it will be difficult to play the performance of the partial ratio material in the end; by using the above method, the material forms uniform primary grains on the first platform, grows into relatively common large crystals on the second platform, and repairs the growth on the third platform to obtain crystals with uniform size and complete structure. Finally, the lithium-nickel mixing is greatly suppressed, so that the partial ratio medium-high nickel material can fully play a better performance than the conventional NCM622 material.
[0013] Preferably, the dopant A at least comprises a compound containing niobium; The coating agent B at least comprises a compound containing boron element; The coating agent C at least includes a compound containing silicon.
[0014] Preferably, the dopant A is a compound containing niobium and a compound containing zirconium, and the mass of the zirconium in the compound containing zirconium is 500 to 1500 ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The mass of the niobium element in the compound containing the niobium element is 500 to 1500 ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The coating agent B is a compound containing boron, and the mass of the boron in the compound containing boron is 400-600ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The coating agent C is a compound containing silicon, and the mass of silicon in the compound containing silicon is 800-1200ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0015] Preferably, in the dopant A, the ratio of the mass of niobium in the compound containing the niobium element to the mass of zirconium in the compound containing the zirconium element is 1:1.
[0016] In addition, the present application also discloses a high-capacity and high-rate polycrystalline ternary positive electrode material, which is prepared by the above-mentioned method for preparing the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0017] In addition, the present application also discloses a lithium-ion battery containing the above-mentioned high-capacity and high-rate polycrystalline ternary positive electrode material.
[0018] Compared with the prior art, the present invention has the following advantages: The present application reduces the melting point of the lithium source by adding the dopant A to the material before the primary sintering, thereby improving the penetration of lithium in the material, thereby making the lithium distribution more uniform. At the same time, since the dopant A can enter the lattice of the primary sintered material and play a stabilizing role, it can also effectively suppress the adverse effects of lithium-nickel mixing on the positive electrode material. At the same time, due to the fluxing effect of dopant A, it is not necessary to maintain high temperature sintering throughout the first sintering process. As the first insulation platform with relatively low temperature, the reactants (Li2O, NCMO) decomposed during the sintering process can undergo a preliminary reaction. The mild reaction at this relatively low reaction temperature can obtain primary grains with uniform size and complete structure, which lays a good foundation for the sufficient growth of grains under subsequent high temperature conditions, and finally it is easy to obtain a finished positive electrode material with uniform primary particle size and complete lattice. Further, the second insulation platform with a relatively high temperature makes it easier for the dopant A to enter the lattice of the positive electrode material. At the same time, the second insulation platform with a relatively high temperature can promote the rapid growth of the grains so that the grains grow into primary particles with a volume close to the expected target in a short time; finally, the growth of the grains is further promoted by cooling and sintering. More importantly, the third insulation platform with a relatively long time can inhibit the lithium-nickel mixing phenomenon and repair the internal defects of the primary particles due to its relatively low temperature, thereby improving the structural stability of the primary particles; At the same time, the present application coats the surface of a calcined material. On the one hand, both coating agents can form a fast ion coating layer on the surface of the positive electrode material, which not only improves the protection ability of the positive electrode material, but also can improve the rate performance of the material to a certain extent. In addition, some elements in the coating layer will also partially enter the lattice to further repair the internal defects of the primary particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a scanning electron microscope image of the positive electrode material prepared in Example 1; Figure 2 for Figure 1 Scanning electron microscope image after twice magnification; Figure 3 This is a scanning electron microscope image of the positive electrode material prepared in Example 2; Figure 4 for Figure 3 Scanning electron micrograph at twice the magnification. DETAILED DESCRIPTION
[0020] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0021] Example 1 Step 1: Prepare nickel-cobalt-manganese hydroxide precursor (Ni 0.67 Co 0.13 Mn 0.20 The total molar number of nickel, cobalt and manganese in (OH)2 is 1.03:1, the nickel, cobalt and manganese precursor is mixed with the lithium source and the dopant A, and sintered once to obtain a single-fired material; The primary sintering is specifically as follows: The temperature was raised to the first insulation platform at a rate of 1.5°C / min, the temperature of the first insulation platform was 680°C, and the insulation time was 2h; The temperature was raised to the second insulation platform at a rate of 0.9°C / min, the temperature of the second insulation platform was 880°C, and the insulation time was 2h; The temperature was raised to the third insulation platform at a rate of 0.9°C / min, the temperature of the third insulation platform was 770°C, and the insulation time was 5h; The dopant A is niobium pentoxide, and the mass of niobium element in niobium pentoxide is 2000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary cathode material; Step 2: The first-fired material is crushed, then mixed with coating agent B and coating agent C, placed in a muffle furnace, heated to 300°C at a heating rate of 2°C / min in an air atmosphere, secondary sintered for 4 hours, and then cooled to room temperature to obtain a high-capacity and high-rate polycrystalline ternary cathode material; The coating agent B is boric acid, and the mass of the boron element in the boric acid is 500ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The coating agent C is fumed silica, and the mass of silicon element in the fumed silica is 1000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0022] Example 2 Step 1: Prepare nickel-cobalt-manganese hydroxide precursor (Ni 0.67 Co 0.13 Mn 0.20 The total molar number of nickel, cobalt and manganese in (OH)2 is 1.03:1, the nickel, cobalt and manganese precursor is mixed with the lithium source and the dopant A, and sintered once to obtain a single-fired material; The primary sintering is specifically as follows: The temperature was raised to the first insulation platform at a rate of 1.5°C / min, the temperature of the first insulation platform was 660°C, and the insulation time was 2.5h; The temperature was raised to the second insulation platform at a rate of 0.9°C / min, the temperature of the second insulation platform was 850°C, and the insulation time was 2.5h; The temperature was raised to the third insulation platform at a rate of 0.9°C / min. The temperature of the third insulation platform was 750°C and the insulation time was 6h. The dopant A is niobium pentoxide, and the mass of niobium element in niobium pentoxide is 3000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary cathode material; Step 2: The first-fired material is crushed, then mixed with coating agent B and coating agent C, placed in a muffle furnace, heated to 250°C at a heating rate of 2°C / min in an air atmosphere, secondary sintered for 5h, and then cooled to room temperature to obtain a high-capacity and high-rate polycrystalline ternary cathode material; The coating agent B is boric acid, and the mass of the boron element in the boric acid is 600ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The coating agent C is fumed silica, and the mass of silicon element in the fumed silica is 1200ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0023] Example 3 Step 1: Prepare nickel-cobalt-manganese hydroxide precursor (Ni 0.67 Co 0.13 Mn0.20 The total molar number of nickel, cobalt and manganese in (OH)2 is 1.03:1, the nickel, cobalt and manganese precursor is mixed with the lithium source and the dopant A, and sintered once to obtain a single-fired material; The primary sintering is specifically as follows: The temperature was raised to the first insulation platform at a rate of 1.5°C / min, the temperature of the first insulation platform was 700°C, and the insulation time was 1.5h; The temperature was raised to the second insulation platform at a rate of 0.9°C / min, the temperature of the second insulation platform was 900°C, and the insulation time was 1.5h; The temperature was raised to the third insulation platform at a rate of 0.9°C / min, the temperature of the third insulation platform was 790°C, and the insulation time was 4h; The dopant A is niobium pentoxide, and the mass of the niobium element in the niobium pentoxide is 1000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary cathode material; Step 2: The first-fired material is crushed, then mixed with coating agent B and coating agent C, placed in a muffle furnace, heated to 350°C at a heating rate of 2°C / min in an air atmosphere, secondary sintered for 3h, and then cooled to room temperature to obtain a high-capacity and high-rate polycrystalline ternary cathode material; The coating agent B is boric acid, and the mass of the boron element in the boric acid is 400ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The coating agent C is fumed silica, and the mass of silicon element in the fumed silica is 800ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0024] Example 4 The method is substantially the same as Example 1, except that the dopant A is a mixture of niobium pentoxide and zirconium oxide, and the mass of the niobium element in the niobium pentoxide is 1000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary cathode material; The mass of zirconium element in zirconium oxide is 1000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0025] Example 5 The method is substantially the same as Example 1, except that the dopant A is a mixture of niobium pentoxide and zirconium oxide, and the mass of the niobium element in the niobium pentoxide is 500ppm of the total mass of the high-capacity and high-rate polycrystalline ternary cathode material; The mass of zirconium element in zirconium oxide is 1500ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0026] Example 6 The method is substantially the same as Example 1, except that the dopant A is a mixture of niobium pentoxide and zirconium oxide, and the mass of the niobium element in the niobium pentoxide is 1500ppm of the total mass of the high-capacity and high-rate polycrystalline ternary cathode material; The mass of zirconium element in zirconium oxide is 500ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0027] Example 7 It is basically the same as Example 1, except that the dopant is zirconium oxide, and the mass of zirconium element in zirconium oxide is 2000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0028] Example 8 The same as Example 1, except that the chemical formula of the nickel-cobalt-manganese precursor is Ni 0.6 Co 0.2 Mn 0.2 (OH)2.
[0029] Example 9 The same as Example 1, except that the chemical formula of the nickel-cobalt-manganese precursor is Ni 0.33 Co 0.33 Mn 0.33 (OH)2.
[0030] Example 10 The same as Example 1, except that the chemical formula of the nickel-cobalt-manganese precursor is Ni 0.8 Co 0.1 Mn 0.1 (OH)2; It should be noted that, in this embodiment, considering the reaction efficiency, lithium hydroxide is used instead of lithium carbonate as the lithium source, and the molar number of lithium element in lithium hydroxide is the same as that of nickel cobalt manganese hydroxide precursor (Ni 0.8 Co 0.1 Mn 0.1 The total molar ratio of nickel, cobalt and manganese in (OH)2) is 1.03:1.
[0031] Embodiment 11 The method is substantially the same as Example 1, except that the dopant A is a mixture of niobium pentoxide and yttrium oxide, and the mass of the niobium element in the niobium pentoxide is 1000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary cathode material; The mass of yttrium element in yttrium oxide is 1000ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
[0032] Comparative Example 1 It is basically the same as Example 1, except that the primary sintering process is specifically as follows: The temperature was raised to the first insulation platform at a rate of 1.5°C / min, the temperature of the first insulation platform was 680°C, and the insulation time was 2h; The temperature was raised to the second insulation platform at a heating rate of 0.9°C / min. The temperature of the second insulation platform was 880°C and the insulation time was 7h.
[0033] Comparative Example 2 It is basically the same as Example 1, except that the primary sintering process is specifically as follows: The temperature was raised to the first insulation platform at a rate of 1.5°C / min, the temperature of the first insulation platform was 680°C, and the insulation time was 2h; The temperature was raised to the second insulation platform at a rate of 0.9°C / min, the temperature of the second insulation platform was 770°C, and the insulation time was 5h; The temperature was raised to the third insulation platform at a heating rate of 0.9°C / min. The temperature of the third insulation platform was 880°C and the insulation time was 2h.
[0034] Comparative Example 3 It is basically the same as Example 1, except that the primary sintering process is specifically as follows: The temperature was raised to the first insulation platform at a rate of 0.9°C / min, the temperature of the first insulation platform was 880°C, and the insulation time was 2h; The temperature was raised to the second insulation platform at a rate of 0.9°C / min, the temperature of the second insulation platform was 770°C, and the insulation time was 5h; The temperature was raised to the third insulation platform at a heating rate of 1.5°C / min. The temperature of the third insulation platform was 680°C and the insulation time was 2h.
[0035] Comparative Example 4 The method is substantially the same as Example 1, except that dopant A (niobium pentoxide) is not added in step 1.
[0036] Comparative Example 5 It is basically the same as Example 1, except that the coating agent B (boric acid) is not added in step 1.
[0037] Comparative Example 6 It is basically the same as Example 1, except that the coating agent C (fumed silica) is not added in step 1.
[0038] Comparative Example 7 Step 1: Prepare nickel-cobalt-manganese hydroxide precursor (Ni 0.67 Co 0.13 Mn 0.20 The total molar number of nickel, cobalt and manganese in (OH)2 is 1.03:1, the nickel, cobalt and manganese precursor is mixed with the lithium source, and sintered once to obtain a single-fired material; The primary sintering is specifically as follows: The temperature was raised to the first insulation platform at a rate of 1.5°C / min, the temperature of the first insulation platform was 680°C, and the insulation time was 2h; The temperature was raised to the second insulation platform at a rate of 0.9°C / min, the temperature of the second insulation platform was 880°C, and the insulation time was 2h; The temperature was raised to the third insulation platform at a rate of 0.9°C / min, the temperature of the third insulation platform was 770°C, and the insulation time was 5h; Step 2: Crush the first-fired material, put it into a muffle furnace, heat it to 300°C at a heating rate of 2°C / min in an air atmosphere, perform secondary sintering for 4 hours, and then cool it to room temperature to obtain a polycrystalline ternary positive electrode material.
[0039] Comparative Example 8 It is basically the same as Comparative Example 7, except that the chemical formula of the nickel-cobalt-manganese precursor is Ni 0.6 Co 0.2 Mn 0.2 (OH) 2。
[0040] Comparative Example 9 It is basically the same as Comparative Example 7, except that the chemical formula of the nickel-cobalt-manganese precursor is Ni 0.33 Co 0.33 Mn 0.33 (OH)2.
[0041] Comparative Example 10 It is basically the same as Comparative Example 7, except that the chemical formula of the nickel-cobalt-manganese precursor is Ni 0.8 Co 0.1 Mn 0.1 (OH)2; It should be noted that, in this embodiment, considering the reaction efficiency, lithium hydroxide is used instead of lithium carbonate as the lithium source, and the molar number of lithium element in lithium hydroxide is the same as that of nickel cobalt manganese hydroxide precursor (Ni 0.8 Co 0.1 Mn 0.1 The total molar ratio of nickel, cobalt and manganese in (OH)2) is 1.03:1.
[0042] Performance test: The polycrystalline ternary cathode materials prepared in the above embodiments and comparative examples were subjected to electrochemical analysis of button batteries, mainly comparing the discharge capacity and 1C cycle performance at conventional voltage, the discharge capacity at high rate and the capacity retention rate; The lithium battery cycle life test method is: the capacity retention rate of the button battery after 100 cycles of 1C, the test standard is: voltage 3.0V-4.3V, charge and discharge rate 1C, temperature 25℃, nominal specific capacity 180mAh / g; The lithium battery rate performance test method is: the first cycle capacity of button batteries at different rates, the test standard is: 3.0-4.3V, the temperature is 25℃, the charge and discharge rates are: 0.1C, 0.5C, 1C, 3C, and the nominal specific capacity is 180mAh / g; The test results are shown in Table 1: Table 1 0.1C capacity / mAh / g 1C capacity / mAh / g 3C capacity / mAh / g 1C50th / mAh / g 50-week retention rate 100-week retention rate Example 1 200.1 180.0 168.2 174.1 96.7% 94.2% Example 2 199.3 179.5 167.4 173.2 96.5% 93.9% Example 3 199.9 179.7 167.8 173.3 96.4% 94.0% Example 4 202.5 182.2 169.7 179.6 98.6% 95.8% Example 5 200.3 180.8 168.5 174.4 96.5% 94.3% Example 6 200.4 181.3 168.7 174.7 96.4% 94.1% Example 7 198.8 178.1 165.3 170.5 95.7% 93.2% Example 8 189.6 172.5 161.4 168.2 97.5% 95.5% Example 9 170.7 150.6 140.2 145.2 96.4% 95.3% Example 10 211.5 192.2 182.9 185.8 96.7% 95.5% Embodiment 11 198.3 177.1 165.3 171.9 97.1% 93.2% Comparative Example 1 195.1 176.5 164.7 166.4 94.3% 91.4% Comparative Example 2 192.4 174.3 162.6 159.8 91.7% 90.3% Comparative Example 3 189.3 172 159.8 154.5 89.8% 85.9% Comparative Example 4 196.6 175.7 162.6 159.7 90.9% 90.4% Comparative Example 5 193.7 174.9 160.7 157.3 89.9% 94.3% Comparative Example 6 194.6 175.2 161.3 158.1 90.2% 89.6% Comparative Example 7 192.3 174.4 159.6 154.4 88.5% 85.4% Comparative Example 8 186.2 169.3 154.6 155.3 91.7% 90.3% Comparative Example 9 166.3 145.4 135.2 136.9 94.2% 92.3% Comparative Example 10 205.3 186.5 175.6 172.1 92.3% 90.4%
[0043] Result analysis: 1. It can be seen from Examples 1-3 that when the amount of dopant added, the amount of coating agent added and the process parameters in the preparation process of the polycrystalline ternary positive electrode material are slightly changed, the capacity and cycle performance of Examples 1-3 show certain fluctuations, but the overall fluctuation range is relatively small.
[0044] 2. It can be seen from Example 1 and Examples 4-6 that when niobium and zirconium are co-doped, Example 4 produces a more obvious performance improvement trend relative to Examples 1, 5, and 6. The reason is that zirconium doping can further effectively stabilize the grain boundaries, so that the material can reduce cracks caused by volume expansion and contraction during the charge and discharge process in a high-rate working environment, slow down the erosion of the electrolyte, and thus improve the cycle performance and capacity. Moreover, when the mass ratio between niobium and zirconium is 1:1, this improvement effect is more obvious.
[0045] 3. It can be seen from Examples 1 and 7 that when only zirconium is doped, the capacity and cycle performance of Example 7 show a more obvious downward trend compared with Example 1. It can be seen that the fluxing effect and lattice stabilization effect of niobium in this solution are difficult to be replaced. Even though zirconium also has a certain crystal stabilization ability, it is still difficult to achieve the same or similar effect as niobium doping.
[0046] 4. It can be seen from Examples 1 and 11 that when niobium and yttrium are co-doped, the capacity and cycle performance of Example 11 are neither as good as Example 1 nor as good as Example 4. It can be seen that the improvement of the capacity and cycle performance of the positive electrode material by yttrium in this solution is very limited. It can be seen that not all common metal elements used for doping can exert excellent capacity and cycle performance improvement capabilities.
[0047] 5. It can be seen from Example 1 and Comparative Examples 1-3 that after the three-stage sintering is changed to two-stage sintering, the capacity and cycle capacity of the positive electrode material are reduced. The reason is that the high-temperature sintering time is too long, which will lead to more serious lithium-nickel mixing phenomenon, and then make the crystal structure too fragile; Furthermore, after the sintering method of first heating up, then heating up again, and finally cooling down in this scheme is changed to gradually heating up or gradually cooling down, the capacity and cycle performance of Comparative Examples 2 and 3 are still inferior to those of Example 1; The reason is that during the gradual heating process, the second heat preservation platform originally used for rapid crystal growth is moved to the last step, which will cause the final material to have a lower stability of the crystal structure due to the excessively high temperature of the last heat preservation platform and the excessively rapid crystal growth; When the gradual cooling method is adopted, the lower temperature of the first insulation platform is more suitable for the nucleation stage of polycrystalline materials, and raising the temperature may be more conducive to the growth of crystals. Therefore, it is placed at a higher temperature at the beginning, and the uniformity of the crystal size is more difficult to control; thereby further reducing the capacity and cycle performance of the ternary material.
[0048] 6. It can be seen from Example 1 and Comparative Examples 4-6 that when any one of dopant A, coating agent B, and coating agent C is missing, the capacity and cycle performance of Comparative Examples 4-6 will have a significant downward trend. The reason is that in this solution, dopant A, coating agent B, and coating agent C improve the electrochemical performance of the positive electrode material from three directions, and there is an intrinsic connection between the three, that is, there is a synergistic effect. Therefore, when any one of them is missing, the cycle performance of the positive electrode material will have a downward trend to varying degrees; At the same time, by observing comparative examples 4-6 and comparative example 7 without any treatment, it can be seen that the effect achieved by Example 1 far exceeds the effect that should be achieved by the simple superposition of comparative examples 4-6, which further reflects the synergistic effect between dopant A, coating agent B and coating agent C.
[0049] 7. It can be seen from Example 1, Examples 8-10, and Comparative Examples 7-10 that when this solution is applied to a medium nickel material (LiNi 0.67 Co 0.13 Mn 0.20 O 2) When applied to low-nickel materials, the ability to improve capacity and cycle performance exceeds that of the other three ternary materials. The reason is that when applied to low-nickel materials, because the cobalt and manganese content of low-nickel materials is relatively higher, they themselves have higher stability. Although this solution still has a certain improvement effect when applied to low-nickel materials, the overall improvement effect is relatively small; However, since the high-nickel material has too serious lithium-nickel mixing, it is difficult to produce a significant inhibitory effect even if the present scheme is applied. Although the NCM622 series ternary material, which is also medium-nickel, has a certain improvement after the application of the present scheme, its improvement effect is relatively limited compared with the medium-nickel material with a relatively high proportion. The reason is that compared with the conventional NCM622 material, the medium-nickel material with a relatively high proportion itself has a more serious risk of lithium-nickel mixing. By using the above method, the material forms uniform primary grains on the first platform, grows into relatively common large crystals on the second platform, and repairs and grows on the third platform to obtain crystals with uniform size and complete structure. At the same time, the synergistic effect between the dopant A, the coating agent B, and the coating agent C further improves the stability of the crystal, and finally greatly inhibits the lithium-nickel mixing, so that the medium-high nickel material with a relatively high proportion can fully exert its better performance than the conventional NCM622 material.
[0050] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high-capacity and high-rate polycrystalline ternary cathode material. It is characterized in that The following steps are involved: Step 1: Mixing the nickel-cobalt-manganese precursor with the dopant A and the lithium source, and sintering once to obtain a single-fired material; Step 2: crushing the first-fired material, then mixing it with coating agent B and coating agent C, and sintering it twice to obtain a high-capacity and high-rate polycrystalline ternary positive electrode material; The primary sintering process includes a first heat preservation platform, a second heat preservation platform and a third heat preservation platform; The temperature of the first insulation platform is 660-700°C, and the insulation time is 1.5-2.5h; The temperature of the second insulation platform is 850-900°C, and the insulation time is 1.5-2.5h; The temperature of the third insulation platform is 750-790°C, and the insulation time is 4-6h; The dopant A is selected from at least one of compounds containing niobium, zirconium, yttrium and strontium; The coating agent B is selected from at least one of compounds containing boron and cobalt; The coating agent C is selected from at least one of compounds containing silicon and aluminum.
2. The method for preparing the high-capacity and high-rate polycrystalline ternary cathode material according to claim 1, It is characterized in that The chemical formula of the nickel-cobalt-manganese precursor is Ni X Co Y Mn Z (OH) 2 , where 0.60≤x≤0.70, 0.10≤y≤0.20, 0.20≤z≤0.30 and x+y+z=1.
3. The method for preparing the high-capacity and high-rate polycrystalline ternary cathode material according to claim 1, It is characterized in that The chemical formula of the nickel-cobalt-manganese precursor is Ni X Co Y Mn Z (OH) 2 , where 0.65≤x<0.70, 0.10<y≤0.15, z=0.20 and x+y+z=1.
4. The method for preparing the high-capacity and high-rate polycrystalline ternary cathode material according to claim 1, It is characterized in that The dopant A at least comprises a compound containing niobium; The coating agent B at least comprises a compound containing boron element; The coating agent C at least includes a compound containing silicon.
5. The method for preparing the high-capacity and high-rate polycrystalline ternary cathode material according to claim 1, It is characterized in that The dopant A is a compound containing niobium and a compound containing zirconium, and the mass of the zirconium in the compound containing zirconium is 500-1500ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The mass of the niobium element in the compound containing the niobium element is 500 to 1500 ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The coating agent B is a compound containing boron, and the mass of the boron in the compound containing boron is 400-600ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material; The coating agent C is a compound containing silicon, and the mass of silicon in the compound containing silicon is 800-1200ppm of the total mass of the high-capacity and high-rate polycrystalline ternary positive electrode material.
6. The method for preparing the high-capacity and high-rate polycrystalline ternary cathode material according to claim 5, It is characterized in that In the dopant A, the ratio of the mass of niobium in the compound containing the niobium element to the mass of zirconium in the compound containing the zirconium element is 1:
1.
7. The method for preparing the high-capacity and high-rate polycrystalline ternary cathode material according to claim 1, It is characterized in that During the secondary sintering process, the sintering temperature is 250-350° C. and the sintering time is 3-5 hours.
8. A high capacity and high rate polycrystalline ternary cathode material, It is characterized in that The material is prepared by the method for preparing a high-capacity and high-rate polycrystalline ternary positive electrode material as described in any one of claims 1 to 7.
9. A lithium ion battery, It is characterized in that Contains the high-capacity and high-rate polycrystalline ternary positive electrode material as described in claim 8.
Citation Information
Patent Citations
Ternary polycrystal positive electrode material and preparation method thereof, lithium ion battery and electric device
CN118472220A
Polycrystalline high-nickel ternary positive electrode material, preparation method thereof, positive plate and lithium ion battery
CN111422921A
Boron-coated fluorine-zirconium co-doped ternary positive electrode material, preparation method and application
CN116190609A
Positive electrode material, preparation method thereof and lithium ion battery
CN117080416A
Polycrystal ternary positive electrode material, preparation method thereof and lithium ion battery
CN117410478A
Cited By
Doped positive electrode active material
WO2026139380A1
